STUDENTS' PERCEPTIONS AND MOTIVATION ON THE IMPLEMENTATION OF MBKM AT ENGLISH DEPARTMENT UNIVERSITAS BANDAR LAMPUNG - Akmalina, Shilvia Mulya; Prastyo, Yanuar Dwi (Journal of Education, Linguistics, Literature and Language Teaching, 2023)
Merdeka Belajar-Kampus Merdeka (MBKM), or in English it is translated as Emancipated Learning - Independent Campus, is a new regulation intended to promote students' independence. in developing their interests and motivation in learning. As this MBKM Policy is a new educational policy in Indonesia, research on its implementation and its impact is still much needed. This study aims to: 1) explore English students’ perceptions of the implementation of Merdeka Belajar-Kampus Merdeka Program at the English Department of Universitas Bandar Lampung, 2) explore English students’ intrinsic and extrinsic motivation to participate in Merdeka Belajar-Kampus Merdeka Program at English Department of Universitas Bandar Lampung. The sample of this study is English students at Universitas Bandar Lampung, as many as 25 students participated in the MBKM program. Data was collected using questionnaires and interviews. The results indicated intrinsic and extrinsic factors that influence students to participate in the MBKM program which include: 1) Intrinsic factors (challenging, curiosity, developing self, learning new things, increasing soft and hard skills, being an intelligent student and exploring the ability and knowledge), 2) Extrinsic factors (getting a good job, getting the reward, gaining appreciation/praise from the environment, and get money from the government). Students at Universitas Bandar Lampung believe that MBKM has been successfully implemented and that it has been well worth it. With the MBKM Program, students can receive assistance in the learning process, including the best experience, personal growth, improved English proficiency, optimal learning, and considerable advancement. The MBKM Program's ability to motivate students can have a good effect and aid in their future job growth, self-quality development, and academic success.